Christian Interest Groups in A Religiously Changing United Kingdom: Issues, Strategies, Influence - Gover, Daniel (Politics and religion, 2022)
Christianity is in long-term decline in the United Kingdom, with decreasing levels of affiliation, practice, belief, and social authority. At the same time, however, Britain's churches and the faith they represent remain deeply embedded within culture and society. This paper offers the most comprehensive analysis to date of how the "sector" of UK Christian interest groups—that is, organizations with a Christian character that seek to influence government policy—operates within this changing socio-religious context. Based on survey and interview data, it examines the extent of Christian interest group activity in the UK, before assessing their issue agendas, lobbying strategies, and influence. The results indicate that the activities of Christian interest groups have been affected by decline, but also by Christianity's continued strengths within society. These findings provide a basis for deeper investigation of Christianity's political influence in the UK, and will also have implications beyond this case.